Richard D. Alba 1942–2025: Distinguished scholar of ethnicity and immigrant assimilation and cherished mentor and friend - Philip Kasinitz; Mary C. Waters (Proceedings of the National Academy of Sciences, 2026)
Richard D. Alba, a path-breaking sociologist who studied immigrant assimilation and its impact on mainstream cultures, in the United States and in Western Europe, passed away on June 4, 2025, at the age of 82. His early work rigorously chronicled the upward mobility, suburbanization, intermarriage, and mixed ethnic identities of later-generation European immigrants. He found similar patterns among recent immigrants and the second generation from Latin America, the Caribbean, and Asia. Together with Victor Nee, he developed “neoassimilation” theory, describing a two-way process involving changes among immigrants and the emergence of a multiracial, multicultural mainstream, emphasizing the conditions under which a society can integrate newcomers with less resistance. Alba was a beloved mentor, friend, and colleague to generations of social scientists.